Learning Securely. - Klarreich, Erica (Communications of the ACM, 2016)
The article discusses machine learning and an emerging field focused on exploring vulnerabilities in machine learning algorithms and ways to handle adversarial input by hackers. Topics include the impact of deep neural networks on potential applications and attacks of machine learning, the ability of hackers to transfer adversarial examples from one machine learning model to another, and the need for benchmarks and the integration of security during the development of machine learning algorithms.